2003
DOI: 10.1037/0735-7044.117.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Lack of opioid or dopaminergic effects on unconditioned sexual incentive motivation in male rats.

Abstract: The effects of dopaminergic and opioidergic drugs on sexual incentive motivation were evaluated in sexually inexperienced male rats subjected to a choice procedure. Various parameters of ambulatory activity were recorded as well. Two drugs stimulating dopaminergic neurotransmission, amphetamine and apomorphine, failed to affect sexual incentive motivation, although ambulatory activity was enhanced by amphetamine. The dopamine antagonist cis(Z)-flupenthixol reduced sexual incentive motivation, but only at a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 78 publications
1
18
1
Order By: Relevance
“…The finding that lesioned, sexually naive males that failed to copulate also failed to display receptive female preference is consistent with previous studies demonstrating an effect of sexual experience on the development of preferential approach to a receptive female (for a review see Taylor & Dewsbury, 1990). However, other studies have shown preferences for receptive females in sexually naive males (Agmo, 2003a,b), suggesting that TPP lesions or TPP lesions with exposure to receptive females in naive males interferes with these unconditioned preferences. Collectively, our findings demonstrate that the effects of TPP lesions in sexually naive males involve a deficit in the acquisition of specific aspects of sexual behaviour.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The finding that lesioned, sexually naive males that failed to copulate also failed to display receptive female preference is consistent with previous studies demonstrating an effect of sexual experience on the development of preferential approach to a receptive female (for a review see Taylor & Dewsbury, 1990). However, other studies have shown preferences for receptive females in sexually naive males (Agmo, 2003a,b), suggesting that TPP lesions or TPP lesions with exposure to receptive females in naive males interferes with these unconditioned preferences. Collectively, our findings demonstrate that the effects of TPP lesions in sexually naive males involve a deficit in the acquisition of specific aspects of sexual behaviour.…”
Section: Discussionsupporting
confidence: 76%
“…, 2002). Consistent with this hypothesis, sexual stimuli have high motivational value to both sexually naive and sexually experienced males (Agmo, 2003a,b) and reinforcement and reward are disrupted in both conditions. However, this hypothesis does not account for the TPP independence of drug reward processes in the drug‐dependent and deprived state (Bechara et al ., 1992) when drug motivation and responding are elevated (Dai et al.…”
Section: Discussionmentioning
confidence: 79%
“…0.5 and 1 mg/kg) or amfonelic acid (0.25 and 0.5 mg/kg; i.p.) caused the facilitation of sexual performance in sexually naïve male rats (Agmo and Berenfeld 1990), but did not affect sexual motivation (Agmo 2003). Moreover, amfonelic acid administration resulted in a significantly increased frequency of sniffing and rearing behavior while behaviors associated with sexual behavior (female pursuit and mounting attempts) were not altered (Agmo and Berenfeld 1990).…”
Section: Discussionmentioning
confidence: 93%
“…The same animals evaluated for copulatory behavior were submitted to the sexual incentive motivation test (Agmo, 2003). In this test, a rectangular arena with 50  50  100 cm 3 (height  width  length) that presents two openings that communicate with two small arenas with 25 cm 2 was used.…”
Section: Sexual Incentive Motivation (Sim)mentioning
confidence: 99%